Allometric Equations for Estimating Above Ground Biomass of Sengon (Paraserianthes falcataria) in The Community Forest of Bateh Village, Magelang - Ris Hadi Purwanto; Muhammad Tafakur Azim (Jurnal Ilmu Kehutanan, 2010)
The above ground biomass of Sengon (Paraserianthes falcataria) in the community forest of Bateh Village were estimated by developing allometric equations. To establish the allometric equations, 400 sample trees were measured to determine the relationships between tree height (H) and stem diameter at breast height (D). Eighteen trees of various sizes were cut to measure the above ground biomass (stem, branch and leaves). The results showed that a diameter of 1.3m above the ground (D) alone was a good predictor of tree height (H). When D was combined with H, r2 was improved somewhat for stem, branch and leaves biomass. The relationships among measured tree dimensions drew a simple linear in log-log scale diagrams with r2 over 0.9699, suggesting the growth patterns of tree dimensions were closely interdependent, whereas the allometric equations between D and H was approximated by the hyperbolic relation with r2 over 0.9141. The individual tree equations appear to be applicable over a wide area of sengon in the community forest of Bateh Village, Magelang, Central Java.